PUFatt: Embedded platform attestation based on novel processor-based PUFs - Kong, Joonho; Koushanfar, Farinaz; Pendyala, Praveen K.; Sadeghi, Ahmad-Reza; Wachsmann, Christian (Proceedings - ACM IEEE Design Automation Conference, 2014)
Software-based attestation schemes aim at proving the integrity of code and data residing on a platform to a verifying party. However, they do not bind the hardware characteristics to the attestation protocol and are vulnerable to impersonation attacks. We present PUFatt, a new automatable method for linking software-based attestation to intrinsic device characteristics by means of a novel processor-based Physically Unclonable Function, which enables secure timed (and even) remote attestation particularly suitable for embedded and low-cost devices. Our proof-of-concept implementation on FPGA demonstrates the effectiveness, applicability and practicability of the approach.